Implementasi Pembelajaran Tajwid dan Ketrampilan Membaca Al-Qur’an dalam Materi Al-Qur’an Hadist - Khamid, Abdul; Prasmanita, Dea; Munawaroh, Rif’ah; Zamroni, Ahmad; Nasitoh, One Emi (CV. Creative Tugu Pena, 2020)
This research is an attempt to implement recitation and reading skills of the Qur'an in the material of the Qur'an in class VII students at Al Manar Bener Tengaran MTs. In a teaching and learning activities it is not enough just to transfer knowledge and lecture only. As a teacher must have the skills and methods of learning that are fun so that learning can be achieved effectively and efficiently. The main questions to be answered through this research are (1) How is the implementation of recitation and reading skills of the Qur'an in learning the Qur'an ' an Hadith of grade VII students at MTs Al Manar Bener Tengaran ?, and (2) What are the Obstacles and Solutions in the implementation of recitation and reading skills in the Qur'an in learning the Qur'an Hadith of grade VII students at MTs Al Manar Bener Tengaran ?. To answer these questions, this research uses a qualitative approach by sharing the stages in its research. Based on literature review and research results in the field, the research can conclude that the results of research on the implementation of recitation and reading skills of the Qur'an in learning the Qur'an Hadith VII grade students at MTs Al Manar Bener Tengaran in planning, implementing, evaluating as well as obstacles and solutions in the learning process in accordance with the material taught namely recitation and the skills in reading the Qur'an. Keywords: Tajwid Learning, Reading Skill of Al Qur]an